Challenges of Adolescents in War: а Report from Ukraine’s Frontline Territories - Recka , Karel; Sevcikova , Anna; Loshenko , Oleksandra; Danyliuk , Ivan (Insight: the psychological dimensions of society, 2025)
The study explores the psychosocial challenges faced by children living in frontline territories in Ukraine amid ongoing military conflict. Purpose. The research aims to assess the emotional, social, and physical well-being of these children, identifying key risk factors and coping mechanisms that influence their psychological resilience. The study also seeks to highlight the disparities between parental and child perceptions of well-being and safety. Methods. The quantitative survey was conducted among 259 parents and 79 children from the Kharkiv, Sumy, and Donetsk regions. The data were analyzed to evaluate emotion regulation, social support, perceived safety, sleep patterns, eating habits, and physical health indicators. The study employed descriptive statistical analysis to assess variations in children’s well-being and compare perspectives between parents and children. Results. The study revealed high prevalence of emotional distress, with children exhibiting increased irritability, anxiety, and difficulties in emotional regulation. Notably, 39% of parents reported a decline in their children’s ability to regulate emotions since the conflict began. While social support was available for most children, 30% experienced a reduction in accessible support networks due to displacement and war-related disruptions. The study also identified discrepancies between parental and child perceptions of safety, with parents frequently underestimating children’s feelings of security. Sleep disturbances, appetite changes, and somatic complaints were prevalent, indicating the physiological toll of psychological stress. Despite these adversities, children demonstrated adaptive coping mechanisms, including seeking social interactions, engaging in calming activities, and developing individual strategies for managing stress. Discussion and Conclusions. The study underscores the urgent need for targeted mental health interventions tailored to children in war- affected areas. Holistic support strategies should focus on strengthening emotion regulation, enhancing access to social networks, improving perceived safety, and addressing physical health concerns. Community-based initiatives, parental education, and structured mental health programs can play a pivotal role in mitigating the long-term psychological effects of war- related stress. Addressing these challenges is essential for fostering resilience and ensuring psychological well-being among affected children. Understanding the broader implications of war- related trauma can inform evidence-based policies and interventions, supporting both immediate relief efforts and long-term recovery strategies in post-conflict settings.